2009
DOI: 10.1104/pp.109.149930
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Signaling in Arabidopsis Requires CRN to Localize CLV2 to the Plasma Membrane

Abstract: Stem cell number in shoot and floral meristems of Arabidopsis (Arabidopsis thaliana) is regulated by the CLAVATA3 (CLV3) signaling pathway. Perception of the CLV3 peptide requires the receptor kinase CLV1, the receptor-like protein CLV2, and the kinase CORYNE (CRN). Genetic analysis suggested that CLV2 and CRN act together and in parallel with CLV1. We studied the intracellular localization of receptor fusions with fluorescent protein tags and their capacities for interaction via efficiency of fluorescence res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
361
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(385 citation statements)
references
References 31 publications
20
361
3
1
Order By: Relevance
“…The values represent FRET efficiencies calculated on 10 cells averaged ± SD. A FRET efficiency above 4% is considered to indicate close interaction between proteins for the GFP and mCherry pair (Bleckmann et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The values represent FRET efficiencies calculated on 10 cells averaged ± SD. A FRET efficiency above 4% is considered to indicate close interaction between proteins for the GFP and mCherry pair (Bleckmann et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…5B). A FRET efficiency above 4% is considered to indicate close interaction between proteins for the GFP and mCherry pair (Bleckmann et al, 2010). Therefore, FRET efficiency results indicated that PDI2 and MEE8 interacted in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 For instance, it has been shown that CLV2 was functionally associated with CRN in a receptor complex to perceive the CLV3 signal. 22 Likewise, TMM, forming a receptor complex with ERECTA family members, was found to regulate the proper stomatal distribution and differentiation. 23 Recently, SUPPRESSOR OF BIR1-1 (SOBIR1) was found to associate specifically with various RLPs that either function in plant development or in plant immunity.…”
Section: Introductionmentioning
confidence: 99%
“…7 Genetic approach has demonstrated that these 3 receptor complexes function downstream of CLV3 basically, independently of each other, however, it remains unclear whether they are functionally redundant or each has distinct functions. [6][7][8]15 Previously, we have shown that a synthetic CLV3 peptide, MCLV3 could be a useful tool for investigating downstream components of the CLV signaling pathway. 7,9 Here we report the defects of SAM in a recently identified MCLV3 resistant mutant, pub4, 10 and discuss the possible relationship of its causal gene with the CLV signaling pathway.…”
mentioning
confidence: 99%